Chemical characteristics of non-edible cocoa plant (Theobroma cacao L.) parts and their antiproliferative activity against various cancer cell lines - Baharum, Zainal (2016)
Plants have been a good source of therapeutic agents for thousands of years and an impressive number of modern drugs used for treating cancer diseases are derived from natural sources. Due to its antioxidant properties, which are related to potential anti-cancer effects, the Theobroma cacao (T. cacao) has recently garnered increasing attention and become the subject of research. In the present study, in vitro screening was performed to investigate the antiproliferative activity of fresh non-edible cocoa plant parts such as the cocoa leaf (CL), cocoa bark (CB), cocoa husk (CH), unfermented cocoa shell (UFCS), fermented coco shell (FCS), coco root (CR), cocoa cherelle (CC) and cocoa pith (CP) against several cancer cell lines. Based on the 3- [4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium (MTT) assay results, the CL extract had strong antiproliferative activity against breast cancer (MCF-7) cells and its median inhibitory concentration (IC50) was 41.43 ± 3.26 μg/mL as compared to the other extracts and cell lines. While, antioxidant activity was determined using the 2,2-diphenyl-2-picrylhydrazyl (DPPH), thiobarbituric acid–reactive substances (TBARS) and Folin-Ciocalteu assays. The CR extract had the highest antioxidant activity; its median effective dose (EC50) was 358.3 ± 7.0 μg/mL and total phenolic content was 22.0 ± 1.1 g gallic acid equivalents (GAE)/100 g extract as compared to the other extracts. Only CC extract demonstrated 10.4% ± 1.1 inhibitions in the lipid peroxidation assay. For the phytochemical screening, all extracts showed the presence of saponins, flavonoids, condensed tannins, triterpenes and phytosterols, but no alkaloids or hydrolysable tannins. The CL methanolic extract was purified and identified using bioassay-guided fractionation and gas chromatography-mass spectrometry (GC-MS), respectively. Successive extraction (partitioning) of the CL extract was carried out in hexane followed by dichloromethane and methanol. The CL hexane partitioned fraction showed the highest antiproliferative activity against MCF-7 cells, with an IC50 of 66.7 ± 7.95 μg/mL and further purified using column chromatography, which was divided into 3 steps: fractionation, sub-fractionation and sub-sub-fractionation. The CL sub-fraction (II/SF7) was selected for GC-MS chemical characterisation because it had the highest anti-cancer activity, with an IC50 of 6.36 ± 0.71 μg/mL, and it generated 9 major active compounds with synergistic effects against MCF-7 cells. Eight compounds were known compounds and one unidentified compound was designated ZNL-UPM/MCB-1. The present study marks the first time CL subfraction (II/SF7) from T. cacao leaf extract has been investigated for its antiproliferative activity and apoptotic effect on MCF-7 cells. The MTT assay detected optimum antiproliferative activity in the cells after 48 hours treatment with CL sub-fraction (II/SF7). This sub-fraction exerted significant dose-dependent growth inhibitory effects on the cells by inducing apoptosis, demonstrated by the formation of apoptotic bodies, fragmented DNA ladder, and disruption of the mitochondrial membrane potential. The apoptosis induced by CL sub-fraction (II/SF7) was observed via caspase-3, caspase-8, and caspase-9 activation, indicating involvement of the intrinsic and extrinsic apoptotic pathways. Meanwhile, 3 genes in the MCF-7 cells, namely DDIT3, GADD45G and HRK, showed significant changes in expression after treatment with CL sub-fraction (II/SF7) at the IC75 (45.0 μg/mL) as compared with untreated cells and the IC50 (6.4 μg/mL). The post-treatment fold changes in DDIT3, GADD45G and HRK expression were 3.8, 6.73, and 2.01, respectively. However, the expression levels of some well-known apoptosis-related genes did not show changes. Further, the genes found differentially expressed in the MCF-7 cells could be closely related to apoptosis. Given the overall high IC50 against the normal liver WRL-68 cell line, this study showed that the active methanolic extract of T. cacao leaf had cytotoxic effect on cancer cells, but not on normal cells. The findings determine CL sub-fraction (II/SF7) from the T. cacao has significant potential for breast cancer chemoprevention and can be developed as an anti-cancer agent in the future. The unidentified active compound will be characterized in future studies.